THE CONCEPT, MODEL AND HISTORY OF HEALTH PROMOTING SCHOOL IN POLAND - Leszcz-Krysiak, Agnieszka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents historical development of the Health Promoting School project in Poland and mentions some events crucial for development of this project. Moreover, the focus on the issue mentioned in the topic is driven by a concern to introduce the concept, strategy and model of Health Promoting School and to indicate how important for the health of society is development and practical implementation of the abovementioned project.The concept of health promoting school is based on the general principles of health promotion. There is no one generally accepted definition of such a school. It is defined as a place where all members of school community undertake common activities to improve their health and well-being by means of changing their health behaviors and creating healthy physical and social environment as well as encourage other people in their environment, in particular parents, to undertake similar activities.